A multi-period model for reorganising urban household waste recycling networks. (December 2022) - Zaharudin, Zati Aqmar; Brint, Andrew; Genovese, Andrea
Abstract: Managing waste is a crucial challenge for modern societies. Within the UK government's ambitious environmental targets, municipal Household Waste Recycling Centres represent key facilities. However, local authority budgets are under severe strain due to reductions in central government funding. Therefore, local councils often need to perform reconfigurations of the recycling centres networks, by reducing the number of sites or their opening hours while still ensuring adequate service levels. This paper describes a novel multi-period mathematical programming model for optimising reorganisational actions within Household Waste Recycling Centre networks. The model is tested on a case study based on an English local authority, in order to demonstrate its applicability to a real-world scenario, and its role in supporting decision-makers in deciding the best way to reorganise Household Waste Recycling Centres. Highlights: A model for restructuring Household Waste Recycling Centres networks is proposed. The model is tested on a real-world case from an English local authority. Network reconfiguration scenarios are considered. The model is a viable tool which can be employed for planning purposes.